2009
DOI: 10.1002/bit.22387
|View full text |Cite
|
Sign up to set email alerts
|

Bioproduction of the aroma compound 2‐Phenylethanol in a solid–liquid two‐phase partitioning bioreactor system by Kluyveromyces marxianus

Abstract: The rose-like aroma compound 2-phenylethanol (2-PE) is an important fragrance and flavor ingredient. Several yeast strains are able to convert l-phenylalanine (l-phe) to 2-PE among which Kluyveromyces marxianus has shown promising results. The limitation of this process is the low product concentration and productivity primarily due to end product inhibition. This study explored the possibility and benefits of using a solid-liquid Two-Phase Partition Bioreactor (TPPB) system as an in situ product removal techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 21 publications
3
84
0
Order By: Relevance
“…Over the course of the biotransformation period, 1 g polymer samples were periodically collected and tested for benzyl alcohol and benzaldehyde concentrations using the methanol extraction technique described by Gao and Daugulis (2009), in which the polymer beads are extracted repeatedly with methanol and the concentrations of target molecules determined from mass balances and polymer density.…”
Section: Product Recovery From Polymer Beadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the course of the biotransformation period, 1 g polymer samples were periodically collected and tested for benzyl alcohol and benzaldehyde concentrations using the methanol extraction technique described by Gao and Daugulis (2009), in which the polymer beads are extracted repeatedly with methanol and the concentrations of target molecules determined from mass balances and polymer density.…”
Section: Product Recovery From Polymer Beadsmentioning
confidence: 99%
“…These studies have shown initially promising results with an increase in total benzaldehyde concentration achieved compared to that of single phase systems. However, limitations associated with the use of organic solvents, including potential toxicity to the biocatalyst as well as the negative effect on the flavour/fragrance compound due to fugitive aromas, have led to the use of commodity polymers, which are biocompatible, non-bioavailable as the sequestering phase, chemically inert, and inexpensive (Gao and Daugulis 2009;Khan and Daugulis 2010;Morrish and Daugulis 2008;Prpich and Daugulis 2007). In this work, the biotransformation of benzyl alcohol to benzaldehyde using P. pastoris was investigated using rational polymer selection for sequestering phase selection in a solid-liquid TPPB.…”
Section: Introductionmentioning
confidence: 99%
“…This is higher than 2PE production from other yeast systems presented in the literature using the adsorbants Hytrel, polypropylene glycol 1200, or polystyrene resin 14, 15…”
Section: Resultsmentioning
confidence: 66%
“…In contrast to S. cerevisiae and K. lactis, which are widely used for molecular biology and industrial applications (Mattiazzi et al, 2012;Schaffrath and Breunig, 2000;Schwimmer et al, 2006;Smith and Snyder, 2006;van Leeuwen et al, 2012), K. marxianus has received relatively little attention, although there are an increasing number of reports describing the potential application of K. marxianus for the production of ethanol, biomass, endogenous enzymes and aromatic compounds (Bansal et al, 2008;Fonseca et al, 2008;Gao and Daugulis, 2009;Limtong et al, 2007;Nonklang et al, 2008Nonklang et al, , 2009Rodrussamee et al, 2011;Wittmann et al, 2002) and for protein structural analysis (Watanabe et al, 2012;Yamaguchi et al, 2012aYamaguchi et al, , 2012b. Thus, in the present study, we generated and characterized 79 auxotrophic mutants and identified 35 complementing genes using a novel integrative transformation approach for the development of genetic tools in K. marxianus.…”
Section: Discussionmentioning
confidence: 99%